Why Do Some Users Become Enticed to Cheating in Competitive Online Games? An Empirical Study of Cheating Focused on Competitive Motivation, Self-Esteem, and Aggression - Lee, Sung Je; Jeong, Eui Jun; Lee, Dae Young; Kim, Gyoung Mo (Frontiers in Psychology, 2021)
Cheating, the act of winning in a competition based on unfair advantages over one’s opponents, often occurs in online games (e.g., illegal money exchange, account hacking, exploiting a bug, etc.). With the recent flourishing of competitive tournament games online such as League of Legends (LoL) and Overwatch, cheating has emerged as a serious problem since it not only promotes the de-socialization of gamers but also adversely affects game brands. However, there has little research on this issue in studies on competitive online games. Focused on three psychological factors (i.e., competitive motivation, self-esteem, and aggression) which has been reported to be primarily related to cheating in sports, this paper presents a study that empirically examined the associations between the factors and cheating in competitive online game environments. From survey data of 329 LoL gamers in South Korea, a structural equation model was analyzed. The results showed that gamers with a high degree of competitive motivation are more inclined to cheat in the game. Aggression increased cheating behavior and had a significant relationship with competitive motivation. Self-esteem decreased the degree of cheating but did not affect competitive motivation. Notably, gaming time negatively influenced cheating. The practical implications of these study results were discussed.